ESTABLISHING A MARKET FOR HUMAN ORGANS* IN SOUTH AFRICA PART 2: SHORTCOMINGS IN LEGISLATION AND THE CURRENT SYSTEM OF ORGAN PROCUREMENT** - Magda Slabbert; Hennie Oosthuizen (Obiter, 2022)
The present shortage of transplantable organs in South Africa may be attributed to inadequate legislation and the current system of organ procurement. The Human Tissue Act 65 of 1983, in the interim phase, still prohibits the sale of organs for transplantation. Chapter 8 of the new National Health Act 61 of 2003 will take over this function once it is promulgated. Although the new Act allows the reimbursement of costs incurred in the donation of an organ, it may still not be sufficient to motivate more donors to donate organs in an effort to alleviate the organ shortage. The purpose of this article is to illustrate that the sale of organs and a change in the current system of organ procurement may be a solution. It is also submitted that, should legislation be changed to legalise organ sales, it will be neither an encroachment on the basic principles of medical ethics nor a violation of fundamental rights.